MOF with hydroxynaphthoquinone as organic linker: molecular structure of [Zn(Chlorolawsone)(2)(H2O)(2)] and thermogravimetric studies - Salunke-Gawali, Sunita; Kathawate, Laxmi; Puranik, Vedavati G. (Journal of Molecular Structure, 2012)
Zinc complexes as MOF with hydroxynaphthoquinone as organic linkers are synthesized and characterized. The complexes Zn-1; [Zn(lawsone)(2)(H2O)(2)]center dot 3H(2)O and Zn-2; [Zn(chlorolawsone)(2)(H2O)(2)]center dot H2O, where lawsone is 2-hydroxy-1,4-naphthoquinone and chlorolawsone is 3-chloro-2-hydroxy-1,4-naphthoquinone, serve as hosts for adsorbed water molecules. nu(c=O) shows shift towards lower frequencies similar to 25 cm(-1) in Zn-1 and similar to 35 cm(-1) in Zn-2 in FTIR spectra. (HNMR)-H-1 shows upfield shift in Zn-1 and downfield shift in Zn-2 to the benzenoid ring protons. Bathochromic shift has been observed to the charge transfer band in UV-visible spectra of both complexes. The mass loss of adsorbed water molecules have been observed <100 degrees C in thermogravimetric (TG) studies. Three adsorbed water molecules are present in Zn-1, while one in Zn-2. X-ray diffraction studies of Zn-2 show, distorted octahedral geometry around Zn(II). The two chlorolawsone ligands are in plane with the metal, while water molecules are trans to this plane. Formation of MOF has been observed in the synthesis of Zn-2 with chlorolawsone as organic linkers. The structure is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O hydrogen bonding H-bonding along with Cl center dot center dot center dot pi interactions to form a beautiful MOF architecture. Zn(II) atoms along with organic ligand form a tetramer via O-H center dot O interactions. The shortest Zn center dot center dot center dot Zn distance is 5.04 angstrom. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 3-Chloro-2-hydroxy-1; 4-naphthoquinone; MOF; Naphthoquinone; O-H center dot center dot center dot O hydrogen bonding; Vapochromic behavior; Zinc complexes